Effect of socioeconomic factors on prognosis of breast cancer in young patients - ALKIŞ, HİLAL (My University, 2023)
BACKGROUND: Socioeconomic factors affect the incidence, clinical progress, and prognosis of patients with breast cancer. The aim of the study is to investigate the effect of socioeconomic factors on the prognosis of women with breast cancer at the age of forty years or younger. MATERIALS AND METHODS: A total of 873 breast cancer patients were included in the study. Of these patients, 30.4% were below or at 40 years of age (n=265). Patients’ clinicopathologic features and socioeconomic status (SES) were recorded. Effects of SES on clinicopathologic features were analyzed using qhi-square test. Kaplan-Meier Log Rank test was used for comparison of survival time. RESULTS: Thirty percent of the patients (n=265) was at 40 years of age or younger. Median age of the patients below and over 40 years was 35 (20-40) and 52 (41-85) years, respectively. Invasive ductal carcinoma rate was found higher in younger patients with lower SES. The rate of larger tumors (>5 cm) in younger patients with lower SES was found significantly higher. Although the rate of ER and PR negative tumors was found higher (p<0.04), hormone receptor status was not found affected by SES in younger patients. Median survival time for younger patients with lower and higher SES was found 73 and 116 months, respectively (p=0.035). CONCLUSION: Socioeconomic factors affect the tumor biology and clinical progress of breast cancer patients in all groups of age. Decreased overall survival among young patients with lower SES may be related to late diagnosis and/or difficulties in accessing treatment in addition to presence of unfavorable prognostic factors
Keywords: Breast cancer; prognostic factors; socioeconomic factors; survival; young women